Reviews (Blackfriars, 1934)
Anglo-Catholicism and Orthodoxy. By Dr. W. A. Vissar t'Hooft. The Individual and the Community. By Wen Kwei Lias. Through Fascism to World Power. By M. S. Munro. Hitler. Whence and Whither? By Wickham Steed. Plotin et le Paganisme Religieux. By E. Krakowski. St. Francis of Sales in his Letters. Edited by the Sisters of the Visitation, Harrow-on-the-Hill. With an Introduction by Abbot Butler and a foreword by his Eminence Cardinal Bourne. The Complete Benediction Book for Choirs. By Sir Richard R. Terry. A History of Everyday Things in England. The Rise of Industrialism, 1733–1851. By Marjorie and C. H. B. Quennell. Picasso et ses Amis. By Fernande Olivier. GRAMOPHONE